The giant lipoma pediculated in the falcyform ligament: a case report - Mostafa Sadeghi; Sajad Noorshafiee; Shaghayegh Beshtar; Peyman Rezagholi; Alireza Tavassoli (Babol University of Medical Sciences, 2021)
Background: The lipoma is one of the benign soft tissue tumors that occur most in adulthood. These tumors are one of the common tumors of the limbs, and rarely occur in the abdominal cavity. These masses usually grow slowly and are asymptomatic. Case Presentation: In this article, we present a 23-year-old woman who was referred to a doctor with complaints of abdominal pain and enlargement that occurred in the last 4 months. Following surgery and sampling, it was found that the patient had a lipoma, and the liver was a phlegmatic liver in the liver form. Conclusion: The recurrence and metastasis of the primary tumor histology are not always predictable, and the authors stated that all cases of individual fibrous tumors should be known as potentially malignant.